2019
DOI: 10.1371/journal.pone.0213780
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired hepatic mitochondrial function during early lactation in dairy cows: Association with protein lysine acetylation

Abstract: Early lactation is an energy-demanding period for dairy cows which may lead to negative energy balance, threatening animal health and consequently productivity. Herein we studied hepatic mitochondrial function in Holstein-Friesian multiparous dairy cows during lactation, under two different feeding strategies. During the first 180 days postpartum the cows were fed a total mixed ration (70% forage: 30% concentrate) ad libitum (non-grazing group, G0) or grazed Festuca arundinacea or Mendicago sativa plus supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 77 publications
1
34
1
Order By: Relevance
“…Actually, mitochondria are crucial for cellular energy metabolism processes, including the production of more than 90% of cellular ATP (respiratory chain), tricarboxylic acid cycle, β-oxidation, apoptosis, cell-cycle progression, proliferation and aging, and their dysfunction has been implicated in a wide range of metabolic diseases [36,[42][43][44]. Recently, a significant increase in protein lysine acetylation was found in pasture-fed Holstein-Friesian dairy cows during their early lactation period, accounting for impaired hepatic mitochrondrial function [45]. Low expression of sirtuin 1 (SIRT1), a NAD-dependent histone deacetylase, was indicated to promote hepatic fatty acid synthesis and inhibit fatty acid β-oxidation in dairy cows with mild fatty liver disease [46].…”
Section: Acetylation Of Proteins Locates In the Mitochondria Contribumentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, mitochondria are crucial for cellular energy metabolism processes, including the production of more than 90% of cellular ATP (respiratory chain), tricarboxylic acid cycle, β-oxidation, apoptosis, cell-cycle progression, proliferation and aging, and their dysfunction has been implicated in a wide range of metabolic diseases [36,[42][43][44]. Recently, a significant increase in protein lysine acetylation was found in pasture-fed Holstein-Friesian dairy cows during their early lactation period, accounting for impaired hepatic mitochrondrial function [45]. Low expression of sirtuin 1 (SIRT1), a NAD-dependent histone deacetylase, was indicated to promote hepatic fatty acid synthesis and inhibit fatty acid β-oxidation in dairy cows with mild fatty liver disease [46].…”
Section: Acetylation Of Proteins Locates In the Mitochondria Contribumentioning
confidence: 99%
“…Histone acetyltransferses (HATs) and histone deacetylase (HDACs), as a senor of environmental nutrient and/or energy, balance the acetylation level of target proteins. Mammalian sirtuins (SIRTs) is an important type of NAD-dependent histone deacetylase, such as SIRT1 and SIRT3, were involved in oxidative stress and lipid metabolism regulation [47], and had been proposed as a reliable biomarker and/or therapeutic target for fatty liver disease [45][46][47][48][49]. It suggests that acetylation of mitochondrial protein was an emerging and fundamental mechanism regulating the development of fatty liver disease in dairy cows, through modifying the activities of mitochondrial proteins and overall mitochondrial function [47][48][49].…”
Section: Acetylation Of Proteins Locates In the Mitochondria Contribumentioning
confidence: 99%
“…The fatty liver disease that occurs in dairy cows is a good animal model to reveal the pathology and pathogenesis of NAFLD. More recent study suggests that impaired hepatic mitochondrial function (such as protein lysine acetylation) is closely associated with fatty liver disease during early lactation in dairy cows [43,84]. Determining the crucial genetic factors, such as PPARγ, will also provide essential clues in breeding improvement of fatty liver disease-resistant dairy cattle, eventually contributing to sustainable development of dairy industry.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress may be exacerbated further by ultrastructural mitochondrial lesions, which impair respiratory chain function. Insulin inhibits β-oxidation in the mitochondria through modifying the protein acetylation [83][84][85], resulting in the accumulation of lipids in hepatocytes.…”
Section: Pparγ Indirectly Participates In Lipid Metabolism Via Insulimentioning
confidence: 99%
“…The increased pyruvate, LDH and NADH activities in the plasma of dairy cows with increasing Cr-Met supplementation indicated that hepatic cellular respiration was improved by Cr-Met supplementation. The increased hepatic respiratory rate would lead to a greater level of hepatic gluconeogenesis in dairy cows [31]. Moreover, greater hepatic gluconeogenesis is associated with decreased insulin concentrations in the plasma [32].…”
Section: Discussionmentioning
confidence: 99%